Chemical Studies on Oil-seeds of Forest Origin - Jain, P. P.; Dobhal, N. P.; Pal, Rajendra; Ayyar, K. S. (Indian Forester, 1988)
Results of analysis carried out on 31 forestry species have shown that oil contents of seeds of Abies pindrow. Picea smithiana. Pirus roxburghii, Prinsepia utilis, Schima wallichii and Viburnum cylindricum range from 18.77 to 28.7% and hence may be considered as good for their commercial exploitalion provided sufficient quantities of these seeds can be made available at reasonable rates. Seeds of Adenanthera microsperma and Albizia procera are hard. Hence special type of decorticators are required for separating the kernels. Seeds of Lannea coromandelica and Michelia champaca contain low percentages of kernels the oil contents of which are good. The seeds of other species cannot be considered as oil seeds.